Analisa Faktor Internal Dan Faktor Eksternal Terhadap Minat Mahasiswa Dalam Berwirausaha ( Studi Pada Mahasiswa Feb Universitas Islam Malang Angkatan 2016) - Zumrotul Afifah; Pardiman Pardiman; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2020)
AbstractThis research aims to determine the influence of internal factors and external factors on entrepreneurial interest.The object of this research is a student of the Faculty of Economics and Business of Malang Islamic University, especially in management and accounting, by having samples of 90 students with records that have taken entrepreneurship courses. Sampling techniques use Random Sampling. Data collection techniques using questionnaires and data analysis tools.Based on the results of partial research analysis of internal factors, significant impact on entrepreneurial interest of students with beta coefficient value of 0,467 and sig.0,000. Whereas partially external factors, significant influence on the interest of entrepreneurial students with the value of beta coefficient of external factors of 0,366 and sig.0,000. Simultaneously internal and external factors significantly influence the interest of student entrepreneurship with a beta coefficient value of 87.591 and sig.0,000. Keywords:internal factors, external factors and entrepreneurial interests